(untitled) (Research, Society and Development, 2020)
The authors presented a case of amyloidosis with cardiac involvement in an elderly woman, with a previous history of arterial hypertension, permanent atrial fibrillation and acute heart failure of unknown etiology. The authors presented a case of amyloidosis with cardiac involvement in an elderly woman, with a previous history of arterial hypertension, permanent atrial fibrillation and acute heart failure of unknown etiology. Amyloidosis is a rare and heterogeneous group of diseases, characterized by the extracellular deposit of amyloid protein. There are several types of proteins identified. The most common are tranterritin (TTR) and light chain immunoglobulin (AL), amyloidosis AL, produced in excess by immune cells. Amyloid accumulation can be found anywhere in the body; such as the tongue, heart, adipose tissue, kidney among others. When no underlying disease (secondary amyloidosis) is identified, the term primary or systemic is used. In the latter, the involvement of the heart, with infiltration of the extracellular space by glycoproteins, is very frequent. This work aims to demonstrate the importance of the differential diagnosis of infiltrative cardiomyopathies, in amyloidosis with involvement in other sites such as tongue and cardiac manifestations of the disease, with the diagnosis of transthoracic echocardiography and tongue biopsy diagnosed in a patient at the Cardiology Service of the Army’s Central Hospital- Rio de Janeiro – RJ.